Photoreaction of anthracenyl phosphine oxides: Usual reversible photo- and heat-induced emission switching, and unusual oxidative PC bond cleavage. Issue 30 (25th July 2019) - Katagiri, Kosuke; Yamamoto, Yukina; Takahata, Yuui; Kishibe, Ryoga; Fujimoto, Naoki
Graphical abstract: Highlights: Anthracenyl as photosensitive group. Anthracenyl as photodimerization unit. Anthracenyl as a leaving group. Abstract: Anthracenyl(diphenyl)phosphine oxide and dianthracenylphenylphosphine oxide as photoactive compounds have been synthesized. Anthracenyl group of these compounds indicate the multi-functional roles such as an emission component, a photodimerization component, and a leaving group. When the light irradiation was performed under an oxygen atmosphere, photo-oxidative PC bond cleavage to leave the antharacenyl group was observed. Moreover, phosphonyl radical was produced and then PP bond formation to form diphosphane was observed.